2023
DOI: 10.1186/s12974-023-02753-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise suppresses neuroinflammation for alleviating Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a chronic neurodegenerative disease, with the characteristics of neurofibrillary tangle (NFT) and senile plaque (SP) formation. Although great progresses have been made in clinical trials based on relevant hypotheses, these studies are also accompanied by the emergence of toxic and side effects, and it is an urgent task to explore the underlying mechanisms for the benefits to prevent and treat AD. Herein, based on animal experiments and a few clinical trials, neuroinflammation in AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 288 publications
(300 reference statements)
0
16
0
Order By: Relevance
“…Although we expected that exercise would reduce neuroinflammation, indicated by a decrease in microglia numbers or shifts in microglia morphology, our results do not support this hypothesis. Exercise reduces neuroinflammation in the hippocampus in animal models of Alzheimer's disease (Nichol et al, 2008;Ke et al, 2011;Tapia-Rojas et al, 2016;Zhang et al, 2018;Wang et al, 2023) but our work suggests that in healthy adult mice, chronic treadmill exercise does not regulate microglia count in the dentate gyrus. This suggests exercise has a different mechanism of action in the brain of healthy individuals and that changes in microglia numbers and morphology may not be involved in the beneficial effects of exercise on learning, memory, and neuroplasticity in a healthy model.…”
Section: Exercise Did Not Affect Vascularisation and Had Limited Effe...mentioning
confidence: 55%
“…Although we expected that exercise would reduce neuroinflammation, indicated by a decrease in microglia numbers or shifts in microglia morphology, our results do not support this hypothesis. Exercise reduces neuroinflammation in the hippocampus in animal models of Alzheimer's disease (Nichol et al, 2008;Ke et al, 2011;Tapia-Rojas et al, 2016;Zhang et al, 2018;Wang et al, 2023) but our work suggests that in healthy adult mice, chronic treadmill exercise does not regulate microglia count in the dentate gyrus. This suggests exercise has a different mechanism of action in the brain of healthy individuals and that changes in microglia numbers and morphology may not be involved in the beneficial effects of exercise on learning, memory, and neuroplasticity in a healthy model.…”
Section: Exercise Did Not Affect Vascularisation and Had Limited Effe...mentioning
confidence: 55%
“…The case correlating physical inactivity with AD via a neuroinflammatory mechanism is strong. Recently, Wang et al demonstrated that exercise ameliorates AD by directly and indirectly regulating brain immune responses and promoting hippocampal neurogenesis [41]. Similarly, Seo et al showed that neuroinflammation-mediated microglia activation with pro-inflammatory cytokine release is enhanced by physical inactivity and downregulated by exercise [42].…”
Section: Physical Inactivitymentioning
confidence: 99%
“…A study investigating around 200,000 elderly people over 60 years old in the UK found that genetic factors and lifestyle contributed to dementia onset, whereas even for those with highly pathogenic genes, a healthy lifestyle (not smoking, exercise and a healthy diet) reduced dementia risks [49]. Exercise can ameliorate Alzheimer's disease by regulating the immune response of the central nervous system and promoting hippocampal neurogenesis [50]. Adults performing moderate to vigorous physical activities no less than once each week exhibited a 34-50% risk reduction in cognitive decline and dementia with a duration of 8 to 10 years [51].…”
Section: Strategies For Preventing Dementia Due To Alzheimer's Diseasementioning
confidence: 99%